Improving Brain and Heart Performance as a Basis for Islamic Household Accounting Practices - Septyan, Krisno; Nugraheni, Ranti; Setyawan, Andy; Tri Wahyudi, Chandra (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This community service program aimed to raise awareness among housewives about their roles in household management, with a particular focus on financial responsibilities. Utilizing a lecture-based methodology that integrates humanist and theocentric perspectives, the program emphasized that women should not bear sole responsibility for managing household finances. The initiative also incorporated brain exercises to enhance memory, serving as a tool for recording and retaining important household information. These exercises were designed to improve cognitive function while also promoting emotional well- being, highlighting that true peace (sakinah) in the home stems not from material wealth but from spiritual fulfillment and trust in God. Additionally, the program addressed the growing concerns surrounding online financial risks, such as digital loans and online gambling, educating participants on how these threats could deplete household assets. Ultimately, the program aimed to equip housewives with the knowledge and tools to manage household finances effectively, while fostering a balanced approach that integrates cognitive, emotional, and spiritual health, thus contributing to a harmonious and financially secure family life.